DFT Study and Antiparasitic Activity of Some Azo Dyes Containing Uracil - Nevin Süleymanoğlu; Pınar Kubaşık; Şahin Direkel (Journal of Chemistry)
In this study, for the first time, molecular modeling and antiparasitic activity studies were carried out on some azo dyes containing uracil, 6-amino-5-[(4-nitrophenyl) diazenyl] pyrimidine-2,4 (1H, 3H)-dione (dye I) and 6-amino-5-[(4-bromophenyl) diazenyl] pyrimidin-2,4 (1H, 3H)-dione (dye II), which were resynthesized using the same method in the literature and whose molecular structures were confirmed using FTIR and 1H-NMR methods. In molecular modeling study, all calculations were performed using DFT/B3LYP/6-311++G(d,p) method. The molecular structures of the possible tautomeric forms of dyes I and II were optimized, and their molecular total energies were calculated in the gas phase and DMSO solvent. IR and 1H-NMR spectral data of the possible tautomeric forms of dyes were obtained, and theoretical spectral data were compared with experimental ones. The evaluations show that, for both dyes, the spectral data of the imine-diketo-hydrazone form, which has the lowest energy and is hence determined to be the most stable form, are in agreement with the experimental ones. In antiparasitic activity study, dyes I and II were tested for the first time against parasites Leishmania infantum, Leishmania major, Leishmania tropica promastigotes, and Trichomonas vaginalis trophozoites. In vitro antileishmanial activities against Leishmania promastigotes were tested by microdilution broth assay with Alamar Blue in RPMI 1640 medium, and in vitro trichomonacidal activities against Trichomonas vaginalis parasite were tested using TYM medium. In tests, antileishmanial and trichomonacidal effects were determined by comparing the obtained minimum inhibitory concentration (MIC) and minimum lethal concentration (MLC) values with those obtained for standard drugs (amphotericin B and metronidazole, respectively).